The Relationship Between Indicators of Mathematical Problem-Solving Ability and Performance on The PISA Test: Systematic Literature Review - Dewi Masito Setyo Tuhu; Shelly Morin; Veni Saputri (Didaktika: Jurnal Kependidikan, 2024)
The mathematical problem-solving ability of Indonesian students has declined significantly, as reflected in PISA 2022 results with an average score of 366, far below the OECD average. This decline is attributed to the disruption of the education system during the COVID-19 pandemic and challenges in distance learning. Studies highlight students’ difficulties in connecting math problems to real-life situations and performing basic math operations. Innovative learning methods like flipped classroom and problem-based learning have been shown to improve problem-solving ability. Common errors at comprehension and transformation stages indicate the need for teaching approaches that develop conceptual understanding. This study employs the Systematic Literature Review (SLR) method to analyze 30 articles on mathematical problem-solving within the PISA context (2018–2023). Findings reveal the effectiveness of systematic approaches like Polya's four-step method (see, plan, do, check) and the IDEAL model (identify, define, explore, act, look) in enhancing problem-solving ability. Learning styles and innovative models also play key roles. Adaptive and context-based learning strategies are recommended to improve students' critical thinking and problem-solving abilities. At the policy level, continuous teacher training in innovative methods and improved access to technology are essential. At the classroom level, integrating real-life problems and project-based learning is advised to enhance students’ engagement and skills. These strategies aim to address the challenges and improve PISA performance while fostering critical thinking.